2022
DOI: 10.1177/01937235221134610
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Stakeholders’ Interpretations of Safe Sport

Abstract: In response to numerous highly publicized cases of athlete maltreatment, sport organizations have developed prevention and intervention strategies under the umbrella term of Safe Sport; however, confusion exists about what it does and does not encompass. To better understand what Safe Sport encompasses, this study sought to develop a conceptual framework of Safe Sport, informed by the perspectives of various stakeholders in sport. Using a social constructivist grounded theory approach, semi-structured intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Thus, preventing IV in sport depends on the commitment and collaboration of the collective AHP team members ( 12 , 24 ). Each AHP team member must understands their roles, responsibilities, and obligations in this regard ( 23 , 26 ). Consideration must also be given to their respective perspectives and needs in advancing safe sport ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, preventing IV in sport depends on the commitment and collaboration of the collective AHP team members ( 12 , 24 ). Each AHP team member must understands their roles, responsibilities, and obligations in this regard ( 23 , 26 ). Consideration must also be given to their respective perspectives and needs in advancing safe sport ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…Consideration must also be given to their respective perspectives and needs in advancing safe sport ( 27 ). Evidence-based training for all AHP team members would allow a shared understanding of safe sport and coordinated actions ( 23 ). In this regard, some authors suggested topics that should be universally addressed in training regarding IV in sport (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining three areas were weak, which are (children's nutrition, fruits and vegetables, and carbohydrates). It is important to note that studies by the Central Organization for Statistics and Information Technology [14] show that one of the causes of the spread of severe malnutrition, especially among females, is women's low level of awareness in the area of feeding vulnerable groups of children and pregnant women.…”
Section: Resultsmentioning
confidence: 99%
“…It also helps to reduce the absorption of substances harmful to the body and keeps the non-proliferation of harmful germs in the intestines [13]. g. Water: Everyone knows Water, but few of us drink a sufficient amount of it, and it helps the kidneys to get rid of waste, and it is necessary for all vital and chemical processes in the cells, and it is the basis for the tissues of the body so that it can perform its functions [14]. Women need to exercise more than men, as this is evident through physiological and physical changes during the different stages of growth and development [15].…”
mentioning
confidence: 99%
“…Findings of this nature are indicative of the potential issues of a lack of understanding and awareness of maltreatment from key personnel (e.g., coaches) in sports such as professional football. Thus, in recent times there has been some gradual movement towards exploring the perspective of personnel with an interest in advancing safe sport (32)(33)(34). While this movement has made encouraging advances in understanding the perspective of those in leadership and administrative roles in elite sport, as well as other key personnel such as sport psychology consultants, these studies have not directly explored the perspectives of those directly tasked with safeguarding and welfare (e.g., such as heads of safeguarding/welfare).…”
Section: Defining Maltreatmentmentioning
confidence: 99%